The Famous Five (Five on Kirrin island again) - Blyton, Enid; Eileen, A. Soper (Great Britain Hodder and Stoughton, 1997)
Five on Kirrin Island again; What is Uncle Quentin up to on Kirrin Island? He won't let anyone visit - not even the Famous Five! But he's not alone on George's island - somebody is watching he every move!